Pemanfaatan Metode Problem Based Learning untuk Meningkatkan Prestasi Belajar Aqidah Akhlaq Siswa - Uswatun Hasanah; Mus Mulyadi (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: This study is motivated by the low academic performance of seventh-grade students at MTs Ash-Shiddiqin in Aqidah Akhlaq, with many students failing to meet the Minimum Completion Criteria (KKM) of 75. Objective: The aim of this study is to improve students' academic performance in Aqidah Akhlaq by implementing the Problem Based Learning (PBL) method. Method: This study uses Classroom Action Research (CAR) with a quantitative descriptive approach, involving observation, final tests, and documentation. The subjects of the research are seventh-grade students at MTs Ash-Shiddiqin, located in Cikoneng District, Ciamis Regency. Result: The results show a significant improvement in student performance after the implementation of the PBL method. In the pre-cycle, the average student score was 65.37, with a completion percentage of 22.22%. In Cycle 1, the average score increased to 70.37, with a completion percentage of 44.44%. Cycle 2 showed an average score of 75.74 with a completion percentage of 74.07%, and in Cycle 3, the average score reached 81.48, with a completion percentage of 92.59%. Conclusion: The application of the PBL method can significantly improve student learning outcomes in Aqidah Akhlaq education. Contribution: This study contributes by providing an alternative teaching method that can enhance students' understanding and academic performance in Aqidah Akhlaq and can be applied to other religious education subjects.